Neuro-flight controllers for aircraft using minimal, radial basis function (RBF) neural networks - Chua, Nigel Boon Hong. (2008)
This thesis presents the implementation of a newly developed minimal Radial Basis Function ( RBF ) neural network using the Minimal Resource Allocation Network ( M-RAN ) sequential learning algorithm for flight control system ap-plications. F-8 and F-16 fighter aircraft models are used in this thesis for the neuro-flight control system application studies. Three flight control architectures using M-RAN have been developed in this study.